Influence of different CaF2 contents and heat treatment temperature on apatite-mullite glass ceramics derived from waste materials - Wan Jusoh, Wan Nurshamimi; Matori, Khamirul Amin; Mohd Zaid, Mohd Hafiz; Zainuddin, Norhazlin; Ahmad Khiri, Mohammad Zulhasif; Abdul Rahman, Nadia Asyikin; Abdul Jalil, Rohaniah; Kuld, Esra (Institute of Chemical Technology, 2020)
An apatite-mullite glass ceramics composition derived from clam shell (CS) and soda lime silicate (SLS) glass has been fabricated from a heat treatment process of composition [xCaF2·(45−x)SLS·15CS·20Al2O3·20P2O5], where x is 5, 10, 15 and 20 (wt. %). The result concluded that the Ca and Si elements were found in the CS and SLS glass respectively as a major weight composition, thereby promoting the use of waste materials in the manufacture of glass ceramic samples. Besides, the CaF2 addition lowers the glass transition temperature (Tg) and crystallisation temperature (Tc) of the glass composition. The density and percentage of the linear shrinkage of the samples differs with the addition of CaF2 and various heat treatment temperatures. For the structural properties’ analysis, the formation of fluorapatite with a needle-like microstructure and mullite phase was enhanced with a higher CaF2 content, while the growth of the anorthite phase was observed to occur at a higher heat treatment temperature. Generally, the addition of ahigh CaF2 content with the help of heat treatment in apatitemullite glass ceramics composition greatly promotes the crystallisation of the fluorapatite phase, which is crucial for denture glass ceramics.